Cascade transformations of (±)-citronellal to menthol over extruded Ru-MCM-41 catalysts in a continuous reactor. Issue 23 (23rd October 2020) - Vajglová, Zuzana; Kumar, Narendra; Peurla, Markus; Eränen, Kari; Mäki-Arvela, Päivi; Murzin, Dmitry Yu
Abstract : Catalytic cascade transformations of (±)-citronellal in a continuous mode over bifunctional ruthenium/MCM-41/binder extrudates with different metal location. Abstract : Cascade transformations of (±)-citronellal in a continuous mode were investigated over a bifunctional shaped ruthenium catalyst bearing metal clusters of the size 7–13 nm. Four types of Ru/H-MCM-41 extrudates (1.5 × 10 mm) containing 30% of Bindzil-50/80 colloidal silica binder were prepared varying in metal location and metal-to-acid ratio, while the concentration of Brønsted and Lewis acid sites and textural properties of the final extrudates were comparable. Catalytic tests were performed in the trickle-bed reactor under 70 °C, 10 bar of H2, and the initial reactant concentration in cyclohexane 0.086 mol L −1 for the liquid residence time of 12.5 min. As a reactant, isopulegol, citronellol or (±)-citronellal was used. Metal location in extrudates has a significant effect on the catalytic activity and selectivity especially in terms of isopulegol isomers which content correlated with the metal-to-acid site ratio. Stereoselectivity to the desired (±)-menthol was 68–70%. The highest amount of the desired menthol, 32% yield, was obtained over extrudates where Ru was deposited on the catalytic support, i.e. with the shortest distance between the acid and metal sites, the lowest Brønsted acidity, the lowest Brønsted–Lewis acid sites ratio, the highest specific surface area and the narrowest range of the Ru particle size distribution.